Enhancement of Thermoelectric Performance of n‐Type PbSe by Cr Doping with Optimized Carrier Concentration. Issue 8 (7th January 2015) - Zhang, Qian; Chere, Eyob Kebede; McEnaney, Kenneth; Yao, Mengliang; Cao, Feng; Ni, Yizhou; Chen, Shuo; Opeil, Cyril; Chen, Gang; Ren, Zhifeng
<x xml:space="preserve">Abstract</x> Ti, V, Cr, Nb, and Mo are found to be effective at increasing the Seebeck coefficient and power factor of n‐type PbSe at temperatures below 600 K. It is found that the higher Seebeck coefficients and power factors are due to higher Hall mobility ≈1000 cm2 V−1s−1 at lower carrier concentration. A larger average ZT value (relevant for applications) can be obtained by an optimization of carrier concentration to ≈1018–1019 cm−3. Even though the highest room temperature power factor ≈3.3 × 10−3 W m−1 K−2 is found in 1 at% Mo‐doped PbSe, the highest ZT is achieved in Cr‐doped PbSe. Combined with the lower thermal conductivity, ZT is improved to ≈0.4 at room temperature and peak ZTs of ≈1.0 are observed at ≈573 K for Pb0.9925Cr0.0075Se and ≈673 K for Pb0.995Cr0.005Se. The calculated device efficiency of Pb0.995Cr0.005Se is as high as ≈12.5% with cold side 300 K and hot side 873 K, higher than those of all the n‐type PbSe materials reported in the literature.